Unsteady mixed convective stagnation point flow of hybrid nanofluid in porous medium - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi'ie, Najiyah Safwa; Pop, Ioan; Bachok, Norfifah; Hafidzuddin, Mohd Ezad Hafidz (Springer, 2022)
A new kind of heat transfer fluid called hybrid nanofluid was introduced to enhance the performance of heat exchangers. The flow behavior may be investigated numerically to better comprehend the fluid features. This investigation aspires to unravel the boundary layer flow problem near the stagnation point of unsteady hybrid nanofluid. Such fluid is saturated in a porous medium on a vertical plate with the exertion of mixed convection. The governing model of the flow problem in the form of partial differential equations is simplified into ordinary differential equations by incorporating the appropriate similarity transformation. A built-in finite difference code in MATLAB known as boundary value problem of fourth-order code (bvp4c) is employed to solve the flow problem and execute the numerical solutions. The dual solutions generated by the solver necessitate the implementation of stability analysis, where this analysis indicates only the first solution is stable. As per stable solution, the heat transfer is augmented when the volume concentration of copper is increasingly added to the alumina–water nanofluid suspension. The conversion of the fluid state from laminar to turbulent also can be prevented with the inclusion of a suitable higher volume concentration of copper. The higher value of the first and second resistant parameters due to porous media is considered in this investigation which concludes that these parameters aid in improving the heat transfer and skin friction rates. This investigation has proven hybrid nanofluid's ability to reinforce the heat transfer with the embedment of a porous medium.